ChemInform Abstract: Investigation of Ugi‐4CC Derived 1H‐Tetrazol‐5‐yl‐(aryl) Methyl Piperazinyl‐6‐fluoro‐4‐oxo‐1, 4‐dihydroquinoline‐3‐carboxylic Acid: Synthesis, Biology and 3D‐QSAR Analysis. Issue 41 (7th October 2014) - Chauhan, Kuldeep; Singh, Pratiksha; Kumar, Vikash; Shukla, Praveen K.; Siddiqi, Mohammad Imran; Chauhan, Prem M. S.
Abstract All compounds are tested for their antibacterial activities.